Physical and Enzymatic Perturbation of the Architecture of the Tunica media Destroys its Inherent Thromboresistance - Komorowicz, Erzsebet; McBane, Robert D., II; Fass, David N. (Thrombosis and Haemostasis, 2002)
The media layer of the arterial cryo-cross sections, is defective for vWf-dependent platelet adhesion. Exposure of the same layer by stripping off the most inner portions of the vessel wall results in a highly thrombogenic surface. Stripping or balloon dilation was applied to porcine arteries prior to functional assays. Cryosections of treated or untreated arteries were perfused with porcine blood at 3350 s-1 and platelet deposition was detected by indirect immunofluorescence. Following balloon dilation, vWf-dependent platelet deposition increased; covering 9.08 ± 1.36% of the total media surface area, this value for untreated vessels was 0.88 ± 0.14%. A 10-fold increase was also found in the binding of vWf-coated fluorescent beads to the media. In addition to mechanical procedures, treatment by serine-proteases like trypsin, chymotrypsin and proteinase 3, or by chondroitinase ABC, but not by heparitinase also resulted in a 7-10-fold increase in platelet coverage over the media. Collagen in the media may be complexed with another vessel wall component shielding the vWf-binding sites. Mechanical or biochemical processes unmask these sites, and increase the thrombogenicity of the vessel wall.
Keywords: Vascular media; von Willebrand factor; platelets; proteoglycan; collagen